Both protein and non-protein components in extracellular vesicles of human seminal plasma improve human sperm function via CatSper-mediated calcium signaling - Zhang, Xiaoning; Liang, Min; Song, Dandan; Huang, Rongzu; Chen, Chen; Liu, Xiaojun; Chen, Houyang; Wang, Qingxin; Sun, Xiaoli; Song, Jian; Zhang, Jiali; Kang, Hang; et al. (Human reproduction (Oxford), 2024)
Abstract STUDY QUESTION What is the significance and mechanism of human seminal plasma extracellular vesicles (EVs) in regulating human sperm functions? SUMMARY ANSWER EV increases the intracellular Ca2+ concentrations [Ca2+]i via extracellular Ca2+ influx by activating CatSper channels, and subsequently modulate human sperm motility, especially hyperactivated motility, which is attributed to both protein and non-protein components in EV. WHAT IS KNOWN ALREADY EVs are functional regulators of human sperm function, and EV cargoes from normal and asthenozoospermic seminal plasma are different. Pre-fusion of EV with sperm in the acidic and non-physiological sucrose buffer solution could elevate [Ca2+]i in human sperm. CatSper, a principle Ca2+ channel in human sperm, is responsible for the [Ca2+]i regulation when sperm respond to diverse extracellular stimuli. However, the role of CatSper in EV-evoked calcium signaling and its potential physiological significance remain unclear. STUDY DESIGN, SIZE, DURATION EV isolated from the seminal plasma of normal and asthenozoospermic semen were utilized to investigate the mechanism by which EV regulates calcium signal in human sperm, including the involvement of CatSper and the responsible cargoes in EV. In addition, the clinical application potential of EV and EV protein-derived peptides were also evaluated. This is a laboratory study that went on for more than 5 years and involved more than 200 separate experiments. PARTICIPANTS/MATERIALS, SETTING, METHODS Semen donors were recruited in accordance with the Institutional Ethics Committee on human subjects of the Affiliated Hospital of Nantong University and Jiangxi Maternal and Child Health Hospital. The Flow NanoAnalyzer, western blotting, and transmission electron microscope were used to systematically characterize seminal plasma EV. Sperm [Ca2+]i responses were examined by fluorimetric measurement. The whole-cell patch-clamp technique was performed to record CatSper currents. Sperm motility parameters were assessed by computer-assisted sperm analysis. Sperm hyperactivation was also evaluated by examining their penetration ability in viscous methylcellulose media. Protein and non-protein components in EV were analyzed by liquid chromatography-mass spectrum. The levels of prostaglandins, reactive oxygen species, malonaldehyde, and DNA integrity were detected by commercial kits. MAIN RESULTS AND THE ROLE OF CHANCE EV increased [Ca2+]i via an extracellular Ca2+ influx, which could be suppressed by a CatSper inhibitor. Also, EV potentiated CatSper currents in human sperm. Furthermore, the EV-in [Ca2+]i increase and CatSper currents were absent in a CatSper-deficient sperm, confirming the crucial role of CatSper in EV induced Ca2+ signaling in human sperm. Both proteins and non-protein components of EV contributed to the increase of [Ca2+]i, which were important for the effects of EV on human sperm. Consequently, EV and its cargos promoted sperm hyperactivated motility. In addition, seminal plasma EV protein-derived peptides, such as NAT1-derived peptide (N-P) and THBS-1-derived peptide (T-P), could activate the sperm calcium signal and enhance sperm function. Interestingly, EV derived from asthenozoospermic semen caused a lower increase of [Ca2+]i than that isolated from normal seminal plasma (N-EV), and N-EV significantly improved sperm motility and function in both asthenozoospermic samples and frozen-thawed sperm. LARGE SCALE DATA N/A. LIMITATIONS, REASONS FOR CAUTION This was an in vitro study and caution must be taken when extrapolating the physiological relevance to in vivo regulation of sperm. WIDER IMPLICATIONS OF THE FINDINGS Our findings demonstrate that the CatSper-mediated-Ca2+ signaling is involved in EV-modulated sperm function under near physiological conditions, and EV and their derivates are a novel CatSper and sperm function regulators with potential for clinical application. They may be developed to improve sperm motility resulting from low [Ca2+]i response and/or freezing and thawing. STUDY FUNDING/COMPETING INTEREST(S) This research was supported by the National Natural Science Foundation of China (32271167), the Social Development Project of Jiangsu Province (BE2022765), the Nantong Social and People's Livelihood Science and Technology Plan (MS22022087), the Basic Science Research Program of Nantong (JC22022086), and the Jiangsu Innovation and Entrepreneurship Talent Plan (JSSCRC2021543). The authors declare no conflict of interest.